IMPLEMENTASI GREEN JOB ANALYSIS PADA PERUSAHAAN MANUFACTURE - Abadi, Ferryal; El Barqa, Malviyola (POLITEKNIK LP3I JAKARTA, 2025)
Environmental issues are increasingly important in the manufacturing sector due to the high demand for resource efficiency and environmental impact management. One approach that can support sustainability is green human resource management (GHRM), namely environmentally oriented human resource management policies and practices. This study aims to examine the effect of green job analysis on green recruitment, green training, and green organizational culture in manufacturing companies in Bekasi Regency. The study population was manufacturing employees working in companies that have implemented GHRM policies. The sample was determined using a purposive sampling technique and resulted in 207 respondents, with data analyzed using partial least squares structural equation modeling (PLS-SEM) through SmartPLS. The results showed that the effect of green job analysis on green recruitment, green training, and green organizational culture was proven to be positive and significant. This finding confirms that GHRM practices play an important role in supporting sustainability in the manufacturing sector.